2019
DOI: 10.1037/dev0000585
|View full text |Cite
|
Sign up to set email alerts
|

Black and Latinx adolescents’ developing beliefs about poverty and associations with their awareness of racism.

Abstract: Interpersonal and structural forms of racism contribute to a system of economic stratification in the United States in which children of color are disproportionately likely to be born into poverty and to remain poor as adults. However, only a small body of research has focused on Black and Latinx adolescents' developing beliefs about the causes of poverty or the relationship between such beliefs and their awareness of racism. The present study sought to contribute to this scholarship with a longitudinal invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 86 publications
3
59
0
Order By: Relevance
“…A possible explanation for the lower reliability on this measure is the weak inter-item correlation between two of the measures that comprised this composite: Awareness of Structural Causes of Racism and Beliefs about the Structural Causes of Poverty (see Appendix S1). Moreover, other studies have found a weak relationship between these two measures as well (Seider et al, 2019). Perhaps, then, future research efforts should be wary of merging participants' critical reflection scores on these two different social issues into a single composite, or of forming such composites via unidimensional confirmatory factor analysis in which items are forced to load onto a single latent construct.…”
Section: Limitationsmentioning
confidence: 96%
See 1 more Smart Citation
“…A possible explanation for the lower reliability on this measure is the weak inter-item correlation between two of the measures that comprised this composite: Awareness of Structural Causes of Racism and Beliefs about the Structural Causes of Poverty (see Appendix S1). Moreover, other studies have found a weak relationship between these two measures as well (Seider et al, 2019). Perhaps, then, future research efforts should be wary of merging participants' critical reflection scores on these two different social issues into a single composite, or of forming such composites via unidimensional confirmatory factor analysis in which items are forced to load onto a single latent construct.…”
Section: Limitationsmentioning
confidence: 96%
“…In fact, Steele () argued that educators, parents, and scholars should err on the side of underpreparing students for interpersonal and systemic forms of racism rather than over‐preparing them, else they may continually fall prey to stereotype threat. Yet, the extant research also reports that children of color as young as 6 years old in the United States demonstrate an awareness of stereotypes regarding their own racial group (Bigler, Averhart, & Liben, ), and that awareness of racism increases as youth progress through adolescence (Seider et al, ). Consequently, youth of color in the United States are likely to develop an awareness of racism regardless of the efforts of their parents and educators.…”
Section: Critical Consciousness and Academic Achievementmentioning
confidence: 99%
“…Accordingly, several studies have linked critical action to positive developmental outcomes among marginalized youth. For example, greater involvement in critical action across four years of high school significantly predicted Black and Latinx youth's grade point averages at the end of high school (Seider et al, 2019). For poor and working‐class Black youth, greater involvement in critical action during high school was associated with greater career expectancies in late adolescence, which subsequently predicted occupational attainment in adulthood (Rapa et al, 2018).…”
Section: Reviewing Critical Action and Its Links To Developmental Outmentioning
confidence: 99%
“…The traditional focus on a single domain in developmental inquiry precludes understanding whether critical action may foster positive outcomes (e.g., academic achievement; Seider et al, 2019, or social mobility; Rapa et al, 2018) while simultaneously exposing activists to legal, physical, or psychological costs, which may undermine mental health (Hope et al, 2018). Moreover, as noted earlier, few studies have examined the processes, such as agency (Freire, 1970), that may mediate the link between critical action and positive developmental outcomes in various domains.…”
Section: Questions and Directionsmentioning
confidence: 99%
“…Black youth are exposed to a disproportionate share of contextual risk factors associated with racism and structural inequality, including discrimination, chronic stress, and poverty (Brody et al, 2006;Seider et al, 2019;C. M. Wilson, 2009).…”
Section: Abstract Adolescence Black Youth Intergenerational Relations...mentioning
confidence: 99%